FREEWAT, a Free and Open Source, GIS‐Integrated, Hydrological Modeling Platform. Issue 4 (31st March 2018) - Foglia, Laura; Borsi, Iacopo; Mehl, Steffen; De Filippis, Giovanna; Cannata, Massimiliano; Vasquez‐Suñe, Enric; Criollo, Rotman; Rossetto, Rudy
Abstract : Article impact statement : free and open source tools to boost application and usage of surface−/groundwater models for effective water resource management.